The Influence of Organizational Culture, Organizational Justice and Work Motivation on Organizational Commitment at PT Telkomsel Distributor Independent Power Root Center - Kiki Farida Ferine; Sunaryo Sunaryo (Budapest International Research and Critics University, 2022)
This study aims to look at the influence of organizational culture variables on organizational commitment, look at the influence of organizational justice on organizational commitment and see the influence of work motivation on organizational commitment. The population in this study was all employees of PT TELKOMSEL Distributor Center Akar Daya Mandiri as many as 117 respondents using non-probability sampling. Data that have met the validity and reliability and classical assumptions are processed to produce regression equations namely: Y= 6.974 + 0.018X1 – 0.103X2 + 0.186X3. Where organizational culture has an insignificant influence on organizational commitment because it has a value of the coefficient of tcount > ttable 0.320 > 1.658 at a significant 0.750 < 0.05 so it can be conveyed that the research hypothesis H1 is rejected, Organizational justice does not have a significant influence on organizational commitment because it has a value of the coefficient tcount > ttable – 1,403 > 1.658 at a significant 0.163 < 0.05 so it can be submitted that the H2 research hypothesis was rejected. Work motivation has a significant influence on organizational commitment because it has a coefficient value of tcounting > ttable 3.472 > 1.658 at a significant 0.001 > 0.05 so it can be conveyed that the research hypothesis H3 is accepted. The coefficient of determination indicates that the value of RSquare is 0.440 or equal to 44.40%. This means that, organizational culture, organizational fairness and work motivation are able to explain organizational diversity by the remaining 44.40% explained by other variables that were not included in this study.